Tensile Properties of Nanoclay (NC)-Acrylonitrile Terminated Polybutadiene (ATBN) Modified Epoxy Composites / Siti Nur Liyana Mamauod ... [et al.] - Mamauod, Siti Nur Liyana; Romli1,2, Ahmad Zafir; Mustafa Bakri2, Haizum Faiqah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Brittleness of cured epoxy resins had limited its application in many fields. Modification of epoxy resin is one of the methods to improve the properties of cured epoxy resins. By using a liquid Acrylonitrile Terminated Polybutadiene (ATBN) rubber as a toughening had improved those weaknesses but it sacrifices the tensile properties. Therefore, in order to produce a toughened and strong mechanical properties of the m-Ep resin, nanofiller was introduced. In this work, the effect of nanoclay (NC) on the physical and mechanical properties of ATBN-m-Ep resin was studied. The different amount of NC is added to reinforce the modified epoxy (m-Ep) resin at the loading of 0.05%, 0.3%, 0.5%, 0.7% and 1% by weight. The mechanical properties of the nanocomposites were carried out by conducting the tensile testing. Meanwhile, for the physical testing, the hardness and density measurement was done. Results revealed that all the properties are improved except the tensile strain. An improvement was achieved at low filler loading. Based on the results, the optimum amount of NC was obtained at 0.05 wt. % and it is attributed to the some factors which are a good interaction between nanofiller and m-Ep interfaces and homogeneous dispersion of NC throughout the matrix resulting the formation of exfoliated NC reinforced ATBN-m-Ep composites.